Low Valence Nickelates: Launching the Nickel Age of Superconductivity - Botana, Antia S.; Lee, Kwan-Woo; Norman, Michael R.; Pardo, Victor; Pickett, Warren E. (Frontiers in Physics, 2022)
The discovery of superconductivity in thin films (10 nm) of infinite-layer hole-doped NdNiO_2 has invigorated the field of high-temperature superconductivity research, reviving the debate over contrasting views that nickelates that are isostructural with cuprates are either (1) sisters of the high-temperature superconductors, or (2) that differences between nickel and copper at equal band filling should be the focus of attention. Each viewpoint has its merits, and each has its limitations, suggesting that such a simple picture must be superseded by a more holistic comparison of the two classes. Several recent studies have begun this generalization, raising a number of questions without suggesting any consensus. In this paper, we organize the findings of the electronic structures of n-layered NiO_2 materials (n= 1 to ∞) to outline (ir)regularities and to make comparisons with cuprates, with the hope that important directions of future research will emerge.